Vagally mediated heart rate variability and safety learning: Effects of instructions and number of extinction trials - Wendt, Julia; König, Jörg; Hufenbach, Miriam C.; Koenig, Julian; Thayer, Julian F.; Hamm, Alfons O. (Psychophysiology, 2019)
Extinction of conditioned fear serves as a laboratory model for the mechanism of action underlying exposure treatment with patients suffering from anxiety disorders. Thus, an enhanced understanding of individual differences in extinction learning may help to improve exposure procedures by tailoring treatment plans to the specific needs of the patient. Vagally mediated heart rate variability (vmHRV) is a promising candidate to investigate individual differences in extinction learning because vmHRV is influenced by an inhibitory prefrontal-amygdala network that is similarly implied in extinction learning. Moreover, low levels of vmHRV were previously associated with a higher prevalence of anxiety disorders and a deficit in safety learning. Here, we report on two studies (Study 1: N = 48; Study 2: N = 120) in which we investigated the boundary conditions of the observed association between vmHRV and safety learning as indexed by startle potentiation during instructed or uninstructed extinction training. In Study 1 (conditional discrimination task), we found that low vmHRV levels are associated with higher CS+ potentiation during instructed extinction. In Study 2 (differential cue conditional task), we observed an association between individual vmHRV levels and defensive responding during CS- presentations and, in later instructed extinction trials, during intertrial intervals. These findings indicate an overactive defensive system in individuals with low levels of vmHRV that interferes with their ability to recognize safety and thus is associated with a general perception of unsafety.